Helping Students Make Sense of New Material Through the “I Notice I Wonder” Method - Hotimah, Iis Husnul; Supriatna, Encep (EduBasic Journal: Jurnal Pendidikan Dasar, 2024)
When a student becomes an active doer during the learning process, the advantage of their mindset can be realized. The understanding process started when the teacher created a class atmosphere that attracted student’s curiosity. By throwing questions such as "What do you notice?" and "What do you wonder?", the teacher helps students to look at problems from a wider angle. This will improve students’ confidence, reflective skills, and student’s involvement, it reveals that the aim of studying is not only for completing assignments but also for finding strategies to overcome problems. This will result in a classroom space full of student’s thoughts and ideas that contain curiosity. Sometimes, the process of apperception in the learning process is not fully utilized by the teacher to help students connect the relationship between previous and future material. Thus, students frequently tend to feel confused in understanding the material as a whole. The I Notice I Wonder method was invented to facilitate and ease teachers in utilizing the apperception process as a means to involve students to be a thinker and actor during active learning, and also to commit authority over students to be active doers by appreciating their opinions and ideas. This study focuses on the importance of the teacher’s role during the apperception process in order to help students understand the connectedness between topics of materials.